2015
DOI: 10.15314/tjse.2015112546
|View full text |Cite
|
Sign up to set email alerts
|

Examining secondary school students metaphor perceptions of the concept of physical education lesson

Abstract: The purpose of the present research is examining secondary school 7 th grade students' perceptions of the concept of physical education lesson through metaphors. The present research also tested whether the metaphors produced by the students differ according to gender. The research was conducted on 393 students who study in 7 th grade at three different public secondary schools in the province of Konya in 2014-2015 academic year, fall semester. According to the findings obtained in the research, the students p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sözen and Korur (2019) reported that female students generated more negative metaphors than males but that the difference was statistically insignificant. Köksal and Görücü (2015) also found no gender effect on seventh graders' (n = 393) metaphors for a physical education class, which is probably because seventh graders are in a developmental period where gender does not yet affect their perceptions.…”
Section: Discussionmentioning
confidence: 73%
“…Sözen and Korur (2019) reported that female students generated more negative metaphors than males but that the difference was statistically insignificant. Köksal and Görücü (2015) also found no gender effect on seventh graders' (n = 393) metaphors for a physical education class, which is probably because seventh graders are in a developmental period where gender does not yet affect their perceptions.…”
Section: Discussionmentioning
confidence: 73%
“…When the relevant studies in the literature were examined, it was found that the researchers focused on the physical education lesson (Koksal & Gorucu, 2015;Sofi & Yoncalik, 2015;Karagün, 2021;Güllü, 2021;Stylianou et al, 2013;Carlson, 2001) and the number of studies on teachers was quite low (Sözen & Korur, 2019;Gorucu et al, 2016;Ulas, 2021). In addition, the fact that the students who have just started secondary school are taking the physical education lesson from the physical education teacher for the first time reveals the situation of the students to face a new situation.…”
Section: Introductionmentioning
confidence: 99%